2007
DOI: 10.1242/jeb.007740
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated ecdysteroid on tissue expression of three guanylyl cyclases in the tropical land crab Gecarcinus lateralis: possible roles of neuropeptide signaling in the molting gland

Abstract: SUMMARY Two eyestalk (ES) neuropeptides, molt-inhibiting hormone (MIH) and crustacean hyperglycemic hormone (CHH), increase intracellular cGMP levels in target tissues. Both MIH and CHH inhibit ecdysteroid secretion by the molting gland or Y-organ (YO), but apparently through different guanylyl cyclase(GC)-dependent pathways. MIH signaling may be mediated by nitric oxide synthase (NOS) and NO-sensitive GC. CHH binds to a membrane receptor GC. As molting affects neuropeptide signaling, the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 70 publications
0
26
0
Order By: Relevance
“…Although the increase in Cm-GC-Iβ expression during premolt (Fig. 8B) is not consistent with the hypothesis, it resembles the increase in Gl-GC-Iβ mRNA when the G. lateralis YO is activated by ESA (Lee et al, 2007a). The ecdysteroid titers and the structure of the integument indicated that 13 of the 18 premolt animals were in early premolt (Stage D 0 ; compare ecdysteroid titers in Fig.…”
Section: +mentioning
confidence: 71%
See 4 more Smart Citations
“…Although the increase in Cm-GC-Iβ expression during premolt (Fig. 8B) is not consistent with the hypothesis, it resembles the increase in Gl-GC-Iβ mRNA when the G. lateralis YO is activated by ESA (Lee et al, 2007a). The ecdysteroid titers and the structure of the integument indicated that 13 of the 18 premolt animals were in early premolt (Stage D 0 ; compare ecdysteroid titers in Fig.…”
Section: +mentioning
confidence: 71%
“…Gene expression in YOs from C. maenas and G. lateralis differ in response to ESA. ESA increases Gl-NOS, Gl-GC-Iβ and Gl-GC-III expression in G. lateralis (Lee et al, 2007a;McDonald et al, 2011). By contrast, ESA had little or no effect on Cm-NOS, Cm-GC-Iβ or Cm-GC-III expression in C. maenas nor was there any correlation with hemolymph ecdysteroid levels (Fig.…”
Section: Effects Of Molting On Gene Expressionmentioning
confidence: 88%
See 3 more Smart Citations